Pathologic Genetic Mutations May Correlate with Poor Visual Outcome in Patients with Hydroxychloroquine Retinopathy - Hsun-I. Chiu; Hui-Chen Cheng; Chih-Chiau Wu; Shih-Jen Chen; De-Kuang Hwang; Yi-Ming Huang; Yu-Bai Chou; Po-Kang Lin; Tai-Chi Lin; Ko-Hua Chen; Pei-Yu Lin; Yu-Fan Chang; et al. (Ophthalmology and Therapy)
Abstract Introduction To evaluate the progression rate and identify potential genetic risk factors for poor visual outcome in chloroquine/hydroxychloroquine (CQ/HCQ) retinopathy. Methods Ocular variables, including best-corrected visual acuity (BCVA), hypoautofluorescent area in fundus autofluorescence (FAF) and others were analyzed in patients with a diagnosis of CQ/HCQ retinopathy based on comprehensive ocular and demographic examinations. Whole exome sequencing (WES) was used to investigate the candidate genes associated with inherited retinal diseases. Multivariate analysis was used to analyze the correlation between pathogenic genetic mutation and visual outcome, with poor vision defined as BCVA < 6/12. Results Forty-one patients with an average age of 61.1 ± 13.6 years, daily dose of 8.2 ± 3.6 mg/kg, and treatment period of 12.4 ± 5.6 years were recruited with a mean follow-up of 3.3 ± 2.8 years. Longitudinal observation revealed that eyes continued to have visual acuity decline with a mean progression rate of 0.065 ± 0.164 (ΔLogMAR/year) and structural change with a mean progression rate of 2.16 ± 4.32 (Δhypoautofluorescent area-to-disc-area ratio per year) despite drug cessation. Pathogenic genetic mutations were found in nine of 29 patients (31%) and were associated with poor visual acuity (odds ratio, OR = 17.402, p = 0.024). Elevated HCQ dose and renal disease were related to increased hypoautofluorescent area in FAF (OR = 17.659, p < 0.001, and OR = 7.285, p = 0.007, respectively). Conclusions The study highlights the importance of identifying genetic mutations and monitoring hypoautofluorescent areas in FAF for predicting and managing visual outcomes in patients with CQ/HCQ retinopathy.